Late‐onset, snowstorm‐like appearance of calcium deposits coating a poly(methyl methacrylate) posterior chamber intraocular lens. Issue 6 (June 2016) - Driver, Todd H.; Li, He J.; Sharma, Anushree; Fram, Nicole; Smith, Ronald J.; Werner, Liliana; Mamalis, Nick
Abstract : N/A: An 81‐year‐old man developed decreased vision associated with diffuse precipitates on his poly(methyl methacrylate) (PMMA) posterior chamber intraocular lens (IOL), on his corneal endothelium, and in his anterior chamber approximately 35 years after IOL implantation. Slitlamp evaluation showed diffuse white material on the surface of the IOL, white precipitates on the corneal endothelium, and visible debris in the anterior chamber. The patient had IOL exchange, and pathological analysis showed numerous calcium deposits within the Soemmerring ring that diffusely spread to the anterior surface of the PMMA IOL. This case of diffuse calcium precipitates on the IOL and the corneal endothelium and in the anterior chamber 35 years after implantation shows that even long after IOL implantation, lens epithelium proliferation and metabolism can result in sequestered material that can be released many years later. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.